Transporte jejunal eletrogênico da glicose em ratos com deficiência de niacina. - Victoria, C. R. (My University, 1994)
The active electrogenic absorption of glucose was studied in 12 niacin deficient rats using a method for measuring changes in transmural potential difference across jejunal mucosa. The glucose was infused in 6 different concentrations (2.5; 5.0; 10.0; 20.0; 50.0 and 100.0 mM/L) at a constant rate of 1.7 ml per minute. The apparent kinetic parameters (Km and Pdmax) of active electrogenic transport were obtained graphically from curves of glucose transfer potentials. The results were compared with that obtained in a control group. The curve of glucose transfer potential in niacin deficient group was significantly lower than that of the control group. The apparent Km of niacin deficient group was greater than in the control group (16.1 x 12.7 mM/L). Furthermore, the Pdmax of the deficient group was lower than that of the control group (12.5 x 19.4 mV). The results showed that in niacin deficiency occurs a decreasing of the active electrogenic glucose absorption. One of the possible interpretation of the differences in the kinetic characteristics of electrogenic glucose transport would be a depleted energy supplement for the active transport in the enterocyte of the niacin deficient rats.
Jejunal electrogenic transport of glucose in rats with niacin deficiency
Keywords: drug derivative; glucose; nicotinamide; nicotinic acid; active transport; animal; intestine absorption; jejunum; male; metabolism; nutritional deficiency; rat; rat strain; urine; Animal; Biological Transport, Active; English Abstract; Glucose; Intestinal Absorption; Jejunum; Male; Niacin; Niacinamide; Rats; Rats, Wistar